Fewer invited talks by women in evolutionary biology symposia. (20th June 2013) - Schroeder, J.; Dugdale, H. L.; Radersma, R.; Hinsch, M.; Buehler, D. M.; Saul, J.; Porter, L.; Liker, A.; De, I.; Johnson, P. J.; Santure, A. W.; Griffin, A. S.; et al.
Abstract Lower visibility of female scientists, compared to male scientists, is a potential reason for the under‐representation of women among senior academic ranks. Visibility in the scientific community stems partly from presenting research as an invited speaker at organized meetings. We analysed the sex ratio of presenters at the European Society for Evolutionary Biology (ESEB) Congress 2011, where all abstract submissions were accepted for presentation. Women were under‐represented among invited speakers at symposia (15% women) compared to all presenters (46%), regular oral presenters (41%) and plenary speakers (25%). At the ESEB congresses in 2001–2011, 9–23% of invited speakers were women. This under‐representation of women is partly attributable to a larger proportion of women, than men, declining invitations: in 2011, 50% of women declined an invitation to speak compared to 26% of men. We expect invited speakers to be scientists from top ranked institutions or authors of recent papers in high‐impact journals. Considering all invited speakers (including declined invitations), 23% were women. This was lower than the baseline sex ratios of early‐mid career stage scientists, but was similar to senior scientists and authors that have published in high‐impact journals. High‐quality science by women therefore has low exposure at international meetings, which will constrain Evolutionary Biology from reaching its full potential. We wish to highlight the wider implications of turning down invitations to speak, and encourage conference organizers to implement steps to increase acceptance rates of invited talks.